REPRESENTATION OF EMOTIONAL-EXPRESSIVE LEXICAL UNITS IN BEGIJON AKHMEDOV'S NARRATIVE “THE WANDERER” (American Journal of Interdisciplinary Research and Development, 2023)
The article analyzes the words expressing human emotions in Begijon Akhmedov's narrative “The Wanderer”. Words related to emotion in the work were selected and analyzed from a contextual point of view.